Anxiety and political action in times of the Covid-19 pandemic. (March 2023) - Zevnik, Andreja
Since the beginning of the global Covid-19 pandemic in the spring of 2020 countries across the world have implemented various measures to contain the virus. They have restricted public gatherings, mobility and congregation of people at homes and in public places. These restrictions however did not stop another chain of events – the global Black Lives Matter (BLM) protests. In the summer of 2020 people across the globe mobilised to protest the police killing of George Floyd. In the UK the protest for Black Lives took place in all major cities, but they also continued weekly in smaller communities by 'taking the knee'. What interests me in this contribution is how anxieties experienced during the global pandemic contributed to the mobilisation of large-scale political actions for racial justice and how might we consider anxiety as a mobilising force in political space in times of global pandemic in particular in the context of anti-racist protests such as BLM. This forum contribution opens by considering how global pandemic aided conditions for political action for racial justice, before discussing the role of anxiety in political mobilising. Here I first detailed how anxiety is understood in Lacanian psychoanalysis before considering what it tells us about the BLM protests for racial justice and specifically the removal of the Colston statue during the Bristol protest on June 7 2020.